Nutrition Aware Family Program Through Personal and Environmental Hygiene - Herda Ariyani; Muhammad Anshari; Dewi Nurhanifah; Ridha Putri Anugrahni; Sahla Qorirah; Utin Nurfadila Meywanda (UMBanjarmasin, 2022)
Currently, stunting is a global problem and greatly affects the quality of human resources. Chronic malnutrition for a long time can also cause various health problems that affect quality of life. The purpose of this service is to provide knowledge to 27 mothers at school of PAUD Kasih Bunda about the importance of maintaining personal and environmental hygiene in an effort to prevent stunting in Lok Rawa Village, Mandastana District also to another targets 22 mothers at the East Delima Berangas Posyandu. In addition, an evaluation of the PERMATA BUNDA (Pemberian Makanan Tambahan Untuk Ibu Hamil dan Anak Balita) and SIBERKAT (Simpanan Ibu BERsalin yang bersinergi untuk masyaraKAT) program were carried out at posyandu delima III, Berangas Timur Village, Alalak District, Barito Kuala Regency, South Kalimantan, Indonesia. The method used in this service is educational activities and hand washing practices as well as face to face interviews with the community. The results of this service show that there is an increase in knowledge regarding stunting and how to prevent or overcome it. They hope that the Permata Bunda program can continue to be implemented to support health status in the present and in the future.